The Effect of Physical Activity Program Based on Pender Health Promotion Model on Type 2 Diabetic Middle-Aged Women's Mental Health - Masoumeh Mansourizadeh; Monireh Anoosheh; Anoshiravan KazemNejad (Iranian Association of Health Education and Health Promotion, 2018)
Background and objective: Diabetes is a chronic illness which has serious physical and mental complication. Physical activity is one of the most important factors in preventing the mental complications of chronic illnesses. This study was performed to evaluate the effect of designed program of physical activity based on Pender health promotion model on type 2 diabetic middle-aged women's mental health. Methods: This was a quasi-experimental study carried out on 102 diabetic middle aged women referring to Diabetes Assembly of Varamin randomly put in two groups of case and control in 2016. The tools of study were demographic and Mental Health Middle-aged Woman (MHMW) questionnaire. Program of physical activity based on Pender health promotion model was accomplished for the women in the case group. At the beginning of study and two month after the intervention, mental health of both case and control group were evaluated. The data were analyzed using SPSS16, chi-square, t-test and Mann-Whitney tests. Results: After the intervention, the score of mental health in case group was 188/80 ±16/51 and in control group was 162/82 ±15/05; there was meaningful difference between them (P<0/001). And promotion in mental health of case group was 24/6±6/8 and in control group was 0/51 ±4/3; it indicated meaningful difference between them (P<0/001). Conclusion: The results showed that the designed program of physical activity based on health promotion model has a positive effect on the increasing of diabetic middle-aged women's mental health